2021
DOI: 10.1037/xge0000975
|View full text |Cite
|
Sign up to set email alerts
|

A test of synergy in dynamic system control tasks.

Abstract: Individual performance in controlling complex dynamic systems such as managing production in a company or keeping ecosystems in balance is often suboptimal. In this article, we provide the first unequivocal test of whether groups are superior to individuals when controlling dynamic systems. In addition, we test to what extent performance advantages of groups are simply the result of statistically aggregating a larger number of individual opinions and to what extent they represent true synergy attributable to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Previous experiments conducted with the aI-G design showed strong support for G-I transfer (Schultze et al, , 2021 while only one experiment -under favoring conditions -showed support for differential weighting. In particular, differential weighting did only occur in a task with a population bias, where the judges overestimated the weight of small items presented in front of them .…”
Section: Disentangling G-i Transfer and Differential Weightingmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous experiments conducted with the aI-G design showed strong support for G-I transfer (Schultze et al, , 2021 while only one experiment -under favoring conditions -showed support for differential weighting. In particular, differential weighting did only occur in a task with a population bias, where the judges overestimated the weight of small items presented in front of them .…”
Section: Disentangling G-i Transfer and Differential Weightingmentioning
confidence: 82%
“…Note that G-I transfer is not restricted to quantitative judgment tasks as it has also been observed in a variety of other tasks. In particular, G-I transfer has been previously identified in groups working on collective induction tasks , in groups solving reasoning tasks , and most recently in groups controlling dynamic systems (Schultze, Drewes, & Schulz-Hardt, 2021). Therefore, relying on interacting groups in organizations is an effective way to enhance the individual capabilities of the workforce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation